2022
DOI: 10.17556/erziefd.1172132
|View full text |Cite
|
Sign up to set email alerts
|

Bir Ölçek Geliştirme Çalışması: Ortaokul Öğrencilerinin Sosyal Katılım Becerisi Ölçeği

Abstract: Bu çalışmada ortaokul öğrencilerinin sosyal katılım becerilerini belirleyebilmek için yeni bir ölçek geliştirilmiştir. Araştırma sürecinde öncelikli olarak 90 maddelik bir madde havuzu oluşturulmuştur. Belirlenen maddeler alan uzmanlarının görüşleri doğrultusunda gözden geçirilmiş, kapsam geçerliği sağlanmaya çalışılmıştır. Düzeltmelerden sonra elde edilen taslak ölçek, 2021-2022 öğretim yılının ikinci döneminde Bingöl il merkezindeki ortaokul öğrencilerine uygulanmıştır. Ölçeğin yapı geçerliği faktör analizi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The self-regulation skills of 4-6-Year-Old Children (Mother Form) measures 4-6-year-old children's self-regulation skill according to their mother's view. Erol and Ivrendi (2018) developed this form which includes 20 items assessing the self-regulation skill of 4-6-year-old children in terms of working memory, attention, inhibitory control-emotion, and inhibitory control-behavior. According to Erol and Ivrendi, the highest score is 210 and the lowest score is 20 which get from the whole scale (2018).…”
Section: Self-regulation Skills Of 4-6-year-old Children (Mother Form)mentioning
confidence: 99%
See 2 more Smart Citations
“…The self-regulation skills of 4-6-Year-Old Children (Mother Form) measures 4-6-year-old children's self-regulation skill according to their mother's view. Erol and Ivrendi (2018) developed this form which includes 20 items assessing the self-regulation skill of 4-6-year-old children in terms of working memory, attention, inhibitory control-emotion, and inhibitory control-behavior. According to Erol and Ivrendi, the highest score is 210 and the lowest score is 20 which get from the whole scale (2018).…”
Section: Self-regulation Skills Of 4-6-year-old Children (Mother Form)mentioning
confidence: 99%
“…As measures of internal consistency, the Cronbach alpha value for the scale is calculated at .90. Additionally, the factors of the scale were found that working memory is α =.82; attention is α =.89; inhibitory control-emotion is α =.77 and inhibitory control-behavior is .75 (Erol & Ivrendi, 2018). The resulting validity was calculated .84 and test-retest reliability coefficients were calculated .77.…”
Section: Self-regulation Skills Of 4-6-year-old Children (Mother Form)mentioning
confidence: 99%
See 1 more Smart Citation